Reactivity of belite in calcium sulfoaluminate-based cements - Pérez-Bravo, Raquel; Koufany, Imane; Cuesta, Ana; Bescher, Eric P.; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles (Springer Nature, 2025)
The hydration behavior of belite phase in different cements is not well understood. Belite hydrates very slowly but there are reports with faster hydration kinetics. Here, the hydration behavior of belite phase in a commercial belite calcium sulfoaluminate (BCSA) cement has been investigated. The BCSA cement was hydrated with two water-to-cement ratios, 0.50 and 0.65 and at two temperatures, 20 and 40 °C. Studies of calorimetry, NMR, laboratory X-ray powder diffraction (XRPD), thermal analysis (TA) of the pastes, and mass balance calculations have been performed. The calorimetric and LXRPD studies showed that with sufficient water for the hydration reactions to take place, i.e., w/c = 0.65, the degree of reaction of belite is 30% at 7 days and above 60% at 35 days, at 40 °C. The 29Si and 27Al MAS-NMR and TA studies confirmed the reactivity of belite under conditions of sufficient water (thermodynamic requirement) and at high temperature (kinetic requirement). This was demonstrated by the presence of stratlingite by 27Al MAS-NMR and TA. Finally, it was found that ~ 12 mass% of the added water remains unbound, but it is unavailable for the progression of hydration reactions in the studied experimental conditions.
Keywords: Cemento aluminoso; Hidratación; Belite reactivity; Water-to-cement ratio; Temperature; Calcium sulfoaluminate